The importance of bankruptcy prediction and methods - Daiva Rugenytė; Vida Menciūnienė; Lina Dagilienė (Business: Theory and Practice, 2010)
The analysis based on the scientific studies of literature on bankruptcy procedures shows that companies are announced as insolvent rather too late. In order to secure successful and permanent company‘s activity, it is important to rationally value its financial condition constantly. Scientists tried to find integral method, which credibly allows to predict companies financial problems in time. Applying bankruptcy prediction models is one of the most simple as well as accurate ways for predicting bankruptcy of enterprises. With the help of these models, the threat of bankruptcy could be noticed several years before bankruptcy actually starts. In this paper after the analysis of bankruptcy prediction importance and bankruptcy dynamics in Lithuania, bankruptcy prediction models commonly used in scientific literature are given in a systematic way. If all suggested methodologies are analysed, every enterprise can find the most appropriate methodology to value the stability of its activity.